Intepretasi Ayat-ayat Teologis Muá¸¥ammad al-ShawkÄnÄ« tentang Manusia, Wahyu, dan Iman - Kholid, Abd (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
The article examines typological category of al-Shawk?n??s ?theological product?, which cannot be categorized as a part of Sunn?. This view is hold by Mu?ammad ?usayn al-Dhahab? and Mu?ammad ?Al? Ay?z?. Al-Dhahab? concludes that al-Shawk?n??s theological thought is seen as being Sunn? but his work, Fat? al-Qad?r, is classified as al-Zayd?yah. Ay?z?, on the other side, says that al-Shawk?n??s theology tends to be more similarly rational to al-Zayd?yah and al-Mu?tazilah. The author seeks to discuss the issue by exploring al-Shawk?n??s interpretation of theological verses on free will, pre-destination, and the relevance of revelation and human?s ratio. This study finds that al-Shawk?n??s theological arguments tend to be closely similar to Ahl al-Sunnah?s theological doctrines compare to that of al-Mu?tazilah and al-Zayd?yah although he surroundedly grew up among the very rational al-Zayd?yah. It can be observed, for an instance, in his view of human?s deeds which clearly indicates him as having close position to the thought of al-M?turid?yah Bukh?ra. In terms of the relevance of human?s ratio and the function of revelation, al-Shawk?n??s theological arguments are harmonious with al-Ash?ar?yah?s ideology.